2014
DOI: 10.1007/s11130-014-0413-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Iron Status in Rats on the Absorption of Metal Ions from Plant Ferritin

Abstract: An isolate of lead-ferritin obtained from soybean seeds sprouted in 25 mM of PbNO3 was introduced into the diet of both iron-deficient and iron non-deficient male rats. After a 21-day administration period, statistical differences in the lead accumulation in the femurs of the rats were noted. Iron-deficient rats accumulated more than four times the amount of lead in their bones than rats without iron-deficiency. No further decrease was observed in haemoglobin concentrations in the groups of animals fed with le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
5
10
0
1
Order By: Relevance
“…No statistical differences were observed in the liver coefficients of rats in different groups (Fig. 1c); the similar effect was reported by Zielińska-Dawidziak et al [22]. In summary, no general growth parameters in the REE-Fe groups were significantly different from the normal group, which proves that REE-Fe has positive effect on the healthy state of IDA rats.…”
Section: Organ Coefficients Of Ratssupporting
confidence: 86%
See 1 more Smart Citation
“…No statistical differences were observed in the liver coefficients of rats in different groups (Fig. 1c); the similar effect was reported by Zielińska-Dawidziak et al [22]. In summary, no general growth parameters in the REE-Fe groups were significantly different from the normal group, which proves that REE-Fe has positive effect on the healthy state of IDA rats.…”
Section: Organ Coefficients Of Ratssupporting
confidence: 86%
“…1a). It is often observed that the renal coefficient increased when iron is deficient [22]. The renal coefficient significantly decreased in rats supplemented with REE-Fe.…”
Section: Organ Coefficients Of Ratsmentioning
confidence: 99%
“…32 In contrast to the liver and spleen, kidney hypertrophy was observed in the rats of the IDA group (II), and this effect was also observed by Chen et al and Zielińska-Dawidziak. 22,32 The kidney coefficient of the Fe-YM1504 groups (IV-VI) significantly decreased compared with the IDA group (II) (P < 0.05). The IDA group not treated, the normal group treated with a standard diet, the FeSO 4 group treated with FeSO 4 (2 mg Fe per kg), the LD-YM1504 group, the MD-YM1504 group and the HD-YM1504 group treated with the Fe-YM1504 at 0.5, 2 and 4 mg Fe per kg respectively.…”
Section: Organ Coefficient Changessupporting
confidence: 66%
“…Rats fed with IDD exhibited reduced consumption compared to rats fed with BD (control) (p < 0.05). It is known that one of the most Statistical differences were determined by the student's t-test (p < 0.05) for the depletion period and ANOVA (Dunnett, p < 0.05) for the recovery period common effects of iron deficiency is anorexia and that deficient animals can lose weight [36]. During the recovery period, the amount of food consumed increased in animals re-fed with BD but not in the groups re-fed with BLSD or FSSD.…”
Section: Resultsmentioning
confidence: 99%